Effect Of Points System Implementation Of Conduct On The Formation Of Student Behavior STKIP PGRI Sidoarjo - Agung Kurniawan (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2019)
This study aims to determine the effect of applying the point system rules on the formation of student behavior. This research uses field research using a quantitative descriptive approach. The implementation of this point system rule is effective. This is proven based on the results of the analysis through a percentage, 65.6% obtained. The formation of student behavior is sufficient. This is based on analysis through a percentage, 66.2% obtained. The effect of applying the point system rule states that although low or weak affects the formation of student behavior. This is proven based on data analysis conducted using the product moment formula producing a value of r xy of 0.3543 if the value of r xy is consulted with a table of product moment coefficient at a significant level of 5%: 0.304 and a significant level of 1%